Holland Spoor. - Rodrigo, Evert; Monshouwer, Saskia (Odense : Kunsthallen Brandts Klaedefabrik, 1991)
de Beus, Jan ; Cornèl, Hans ; van der Loo, Martie ; Oldenhof, Erik ; Toscani, Bep
Holland Spoor, Kunsthallen Brandts Klaedefabrik, Odense, 9. februar - 7. april 1991
boek